Орыс сыныптарында қазақ əдебиетін оқытуда сын тұрғысынан ойлауды қолдану - Байлиева, А.Б. (My University, 2016)
Critical thinking is not limited to fact-finding, the mastery of information, but also a certain connection with life, the ability to find the information you use to create new products. Assessment of learning outcomes is based on the critical attitude of his work, classmates, etc.
Keywords: critical thinking; Kazakh literature; the teaching of the Kazakh language